(untitled) - Jagor, Fedor (Manila, 1965)
The Philippines Travel Guide includes a varied selection of preplanned travel routes and a wide variety of useful information. Included in the guide is information on transportation; good-value accommodations; selected local and international restaurants; schedules of festivals and special events; illustrated sections on flora, fauna, and culture; details on outdoor activities such as cycling, diving, hiking, and surfing; and a comprehensive chapter on the native languages.